Integrating numeration in mathematics learning - Virdinarti Putra, Lisa; Sukestiyarno; Masrukan; Widodo, Joko (Edelweiss Applied Science and Technology, 2024)
This research is motivated by the Indonesian numeracy ranking, which is the fifth from the bottom of the PISA numeration. Based on the quality report related to numeracy abilities from several elementary schools in Semarang Regency, it can be seen that the scores of schools with numeracy-related achievements are below the minimum competency, which has an overall average of 1.6 for numeracy at the school level. This study is Research and Development that involves three stages: define, design, and develop. It intends to define the context of integrating numeracy in the management of mathematics learning, identify, and find solutions to integrate numeracy in elementary schools in Semarang Regency. The findings of the research show that (1) the significance of numeracy in the management of mathematics learning; (2) the developments obtained in integrating numeracy are conceptual understanding, problem-solving skills, independent skills, logical thinking, and the capability to integrate the learning to students everyday life; (3) the integration of the management of mathematics learning with numeration into a valid learning tool and textbook for grade V Elementary School, as proven by the results of the lesson plans validation of 3.50 and the validation of textbooks of 3.36.